Blended simulation based medical education: A complex learning/training opportunity - Shahoumian, Armineh; Saunders, Murray N K; Zenios, Maria; Parchoma, Gale; Hanson, Jacky (My University, 2014)
Simulation Based Medical Education (SBME) as an innovative approach in Medical and Professionals Allied to Medicine (PAM) education has received international attention in the past few years to support improvement of patient safety and providing better health care services within hospitals. Blended SBME (B-SBME) is a new instructional model recently introduced into the field, which blends on-line briefing sessions followed by a simulation session, and concluded with immediate face-to-face debriefing sessions. In this paper we discuss the complexity of learning in B-SBME and how individualistic learning theories do not support understanding of all these processes. A shift in theoretical lens to socio-cultural theories may develop our understanding of how we depict and theorise the learning that goes on in B-SBME and whether B-SBME can act as a "boundary crossing tool" and support expanding of learning into clinical setting.
Keywords: Blended learning; Boundary crossing tool; Simulation based medical education; Social Practices Theory